3.2k views
2 votes
What is the solution to the equation One-third (x minus 2) = one-fifth (x + 4) + 2? x = 12 x = 14 x = 16 x = 26

User Larry Lv
by
4.8k points

1 Answer

1 vote

Answer:

x = 26

Explanation:

Given


(1)/(3) (x - 2) =
(1)/(5) (x + 4) + 2

Multiply through by 15 to clear the fractions

5(x - 2) =3(x + 4) + 30 ← distribute and simplify both sides

5x - 10 = 3x + 12 + 30, that is

5x - 10 = 3x + 42 ( subtract 3x from both sides )

2x - 10 = 42 ( add 10 to both sides )

2x = 52 ( divide both sides by 2 )

x = 26

User Viraj Parekh
by
5.1k points